THE INFLUENCE OF LIVE SALE AND FLASH SALE ON REPURCHASE INTENTION IN THE NEW NORMAL ERA ON SHOPEE CUSTOMERS IN PADANG CITY - Wardi, Yunia (STIE Ekuitas, 2022)
This study aims to analyze (1) the effect of live sales on repurchase intentions of Shopee customers in Padang City in the new normal era. (2) The effect of flash sale on repurchase intention of Shopee customers in Padang City in the new normal era. The purpose of this study was to determine the effect of live sales and flash sales on repurchase intentions in the new normal era for Shopee customers in Padang City. This type of research is descriptive quantitative with multiple regression analysis. The population in this study were all Shopee customers in Padang City and the sample in this study were Shopee customers in Padang City who had shopped at least twice during the new normal era and registered on Shopee user accounts. The number of samples in this study were 60 respondents. Data was collected through online questionnaire distribution and data processing was done through SPSS software. The results of this study indicate that (1) Live sale has a positive and insignificant effect on repurchase intentions of Shopee users in Padang City in the new normal era. (2) Flash sale has a positive and significant effect on repurchase intention of Shopee customers in Padang City in the new normal era.